Efektivitas Edukasi Menggunakan Media Vidio Animasi,Leaflet Untuk Meningkatkan Pengetahuan Cuci Tangan Pakai Sabun Dan Mencegah Terjadinya Penyakit Diare:Literature Review - Ilman Abdul Ghani; Ridho Agustin; Ali akmal rustandi; Rigit Nurul Ilmi; Nina Pamela Sari (CV. ALIM'SPUBLISHING, 2026)
Diarrhea is one of the diseases that can be prevented through the implementation of clean and healthy living behaviors, particularly proper handwashing with soap (HWWS). This literature review aims to analyze the effectiveness of educational interventions using animated videos and leaflets in improving knowledge of HWWS and preventing diarrhea. Articles were searched through Google Scholar and Garuda Portal, with a publication range from 2021 to 2026. The review findings indicate that both animated video and leaflet media are effective in increasing students' knowledge regarding HWWS. Animated videos are more engaging because they combine audio and visual elements, while leaflets help participants recall and reinforce the information provided during educational sessions. The improvement in knowledge following educational interventions is expected to encourage better HWWS practices, thereby contributing to the prevention of diarrheal diseases